2012
DOI: 10.1002/eat.22054
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐level and momentary correlates of bulimia nervosa with a history of anorexia nervosa

Abstract: Objective Some investigators have suggested subtyping bulimia nervosa (BN) by anorexia nervosa (AN) history. We examined trait-level and momentary eating-related and psychosocial factors in BN with and without an AN history. Method Interview, questionnaire, and ecological momentary assessment data of eating-related and psychological symptoms were collected from 122 women with BN, including 43 with (BN+) and 79 without an AN history (BN−). Results Body mass index (kg/m2) was lower in BN+ than BN− (p=.001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…Extant literature on diagnostic “crossover” may help to interpret these findings, as previous studies of AN, BN, and BED have demonstrated more severe symptomatology in those with a history of a different ED. 3,10-13,17-18 First, the presence of higher rates of comorbid mood disorders in our BED subgroup with a history of AN/BN is consistent with ED crossover in general, as both AN to BN and BN to AN transitions are associated with depression. 3,17 Second, crossover from AN or BN to BED involves a change in the symptoms required for diagnosis, but not necessarily a change in global ED severity.…”
Section: Discussionsupporting
confidence: 75%
“…Extant literature on diagnostic “crossover” may help to interpret these findings, as previous studies of AN, BN, and BED have demonstrated more severe symptomatology in those with a history of a different ED. 3,10-13,17-18 First, the presence of higher rates of comorbid mood disorders in our BED subgroup with a history of AN/BN is consistent with ED crossover in general, as both AN to BN and BN to AN transitions are associated with depression. 3,17 Second, crossover from AN or BN to BED involves a change in the symptoms required for diagnosis, but not necessarily a change in global ED severity.…”
Section: Discussionsupporting
confidence: 75%
“…People should be assessed for a past history of other eating disorders, especially anorexia nervosa, as this may be associated with increased likelihood of relapse and a poorer outcome in some (but not all) studies (Eckert et al, 1995;Goldschmidt et al, 2013;Mitchison et al, 2013;Vaz-Leal et al, 2011). People should be assessed for a past history of other eating disorders, especially anorexia nervosa, as this may be associated with increased likelihood of relapse and a poorer outcome in some (but not all) studies (Eckert et al, 1995;Goldschmidt et al, 2013;Mitchison et al, 2013;Vaz-Leal et al, 2011).…”
Section: Assessmentmentioning
confidence: 99%
“…These results provide in-the-moment evidence that exercise may serve as a means of down-regulating negative affect among individuals with BN. Additionally, using ecological momentary assessment methodology, Goldschmidt et al (in press) found that individuals with BN and a history of anorexia nervosa (AN), but not those without a history of AN, reported a decrease in negative affect following exercise (although this difference was not statistically significant). This finding tentatively suggests that a history of AN may influence the extent to which exercise is motivated by affect regulation.…”
Section: 1 Hard Exercise and Affect Regulationmentioning
confidence: 99%